2013
DOI: 10.1007/s11103-013-0132-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide analysis of dynamic variations in regulation modes of grapevine microRNAs on their target genes during grapevine development

Abstract: MicroRNAs (miRNAs) play critical regulatory roles mainly through cleaving their target mRNAs or repressing gene translation during plant development. Grapevines are among the most economically important fruit crops with available whole genome sequences. Studies on grapevine miRNAs (Vv-miRNAs) are also widely available. However, studies on the regulation mode of Vv-miRNAs on their target mRNAs during grapevine development have not been studied well, especially at the transcriptome-wide level. Here, six small RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 37 publications
6
41
0
Order By: Relevance
“…Since the key role of miRNAs in regulating fruit and seed development is of great applied interest for crop development (Han et al, 2014), identified a number of conserved and non-conserved grapevine miRNAs responsive to exogenous gibberellin and showed that they play a potential role in mediating gibberellin-induced regulation of berry growth, development and response to various environments. Another study identified six novel miRNAs expressed in berries during exogenous gibberellin application and/or ethylene treatment, supporting a role for miRNAs in grapevine fruit development and ripening (Wang et al, 2014). In line with the growing evidence that miRNAs play critical roles in both biotic and abiotic stress responses, a recent study reported that a diverse set of grapevine miRNAs are cold-inducible and may play an important role in cold stress response (Sun X. et al, 2015).…”
Section: Functional Roles Of Mirnasmentioning
confidence: 82%
“…Since the key role of miRNAs in regulating fruit and seed development is of great applied interest for crop development (Han et al, 2014), identified a number of conserved and non-conserved grapevine miRNAs responsive to exogenous gibberellin and showed that they play a potential role in mediating gibberellin-induced regulation of berry growth, development and response to various environments. Another study identified six novel miRNAs expressed in berries during exogenous gibberellin application and/or ethylene treatment, supporting a role for miRNAs in grapevine fruit development and ripening (Wang et al, 2014). In line with the growing evidence that miRNAs play critical roles in both biotic and abiotic stress responses, a recent study reported that a diverse set of grapevine miRNAs are cold-inducible and may play an important role in cold stress response (Sun X. et al, 2015).…”
Section: Functional Roles Of Mirnasmentioning
confidence: 82%
“…The NAC33 expression profile is generally inversely correlated with that of Vv-miR164, which would be expected for a miRNA target (Sun et al, 2012). The recent transcriptome-wide analysis of grapevine miRNAs in six different organs during development revealed the spatiotemporal expression profile of the miRNAs involved in the predicted miRNA/switch gene pairs (Wang et al, 2014). We were therefore able to confirm that 26 switch genes showed the opposite expression profiles to those of their putative miRNA regulators, e.g., Vv-miR166 and ZFWD2 (VIT_13s0047g01130), Vv-miR172d and caffeic acid 3-O-methyltransferase (VIT_02s0025g02920), and Vv-miR482 and dehydration-responsive protein (VIT_16s0100g00570).…”
Section: Mirnas Are Potential Regulators Of Grapevine Switch Genes: Nmentioning
confidence: 94%
“…All sRNAs sequences from 18nt to 30nt obtained were removed from the vector sequences, then the modified sequences were further subjected to removal of rRNA, tRNA, snRNA, snoRNA and those containing the polyA tails, and finally the remaining sequences were compared against known plant Vvi-miRNAs in the miRBase [33]. Only the high matching (0-3mismatches) sequences were considered as conserved Vvi-miRNAs.…”
Section: Methodsmentioning
confidence: 99%